Independence, Management Motives and Financial Statement Fraud: Role of Earnings Management - Yenny Wati; Teddy Chandra (The Indonesian Journal of Accounting Research, 2022)
This study aimed to look at the direct impact of auditor independence and management motivation upon financial statement fraud, with earnings management acting as a moderator. This study relies on secondary data from manufacturing companies registered on the Indonesia Stock Exchange for the period 2013-2018. This study's data were analyzed using partial least squares and the WarpPLS 5.0 program. The outcomes showed that auditor independence and management motivation (financial target and rationalization) have a positive impact on financial statement fraud and earning management. Earnings management can help to mediate the effect of auditor independence and management motivation (financial target and rationalization) with partial mediation. Our research provides new empirical evidence in providing information about factors that are factors in financial statement fraud that are beneficial for companies and stakeholders as well as assessing activities carried out by organizations or companies. Company management can prevent and detect fraud or manipulation of financial statements early, find out the factors that allow fraud to occur, and control areas that may give rise to fraud. This research can be a reference in making various policies regarding the practice of financial statement fraud in an entity.